Partikel Akhir Kalimatbahasa Jepang Dan Bahasa Indonesia - Wahyuningtias, Hani; Artadi, Ari; Dyaya, Hermansyah (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 24 No 1 (2017): Maret, 2017)
In Japanese, the ending particles of  sentences commonly used in conversations are 'ne', 'yo', 'yone', and 'yona'. The matching of these words in Indonesian are 'ya', 'lho' and 'kan'. Using the methodology of language comparison, the theory of Information Territory, and using the example of sentences collected in Japanese comic that has been translated into Indonesian as a source of data, this study examines more deeply the use and function of ending particles on Japanese sentences 'ne', 'yo', 'yone', and 'yona' with the translation of the words in Indonesian. The results shows that the use of ending particle on a sentence like 'ne', 'yo', 'yone', and 'yona' in conversation is a must, while the use of "ya" "lho" "kan" in Indonesian is arbitrary.